A Pseudomonas aeruginosa PQS quorum-sensing system inhibitor with anti-staphylococcal activity sensitizes polymicrobial biofilms to tobramycin. Issue 7 (21st July 2022) - Murray, Ewan J.; Dubern, Jean-Frédéric; Chan, Weng C.; Chhabra, Siri Ram; Williams, Paul
Summary: As single- and mixed-species biofilms, Staphylococcus aureus and Pseudomonas aeruginosa cause difficult-to-eradicate chronic infections. In P. aeruginosa, pseudomonas quinolone (PQS)-dependent quorum sensing regulates virulence and biofilm development that can be attenuated via antagonists targeting the transcriptional regulator PqsR (MvfR). Here, we exploited a quinazolinone (QZN) library including PqsR agonists and antagonists for their activity against S. aureus alone, when co-cultured with P. aeruginosa, and in combination with the aminoglycoside tobramycin. The PqsR inhibitor, QZN 34 killed planktonic Gram-positives but not Gram-negatives. QZN 34 prevented S. aureus biofilm formation, severely damaged established S. aureus biofilms, and perturbed P. aeruginosa biofilm development. Although P. aeruginosa protected S. aureus from tobramycin in mixed biofilms, the combination of aminoglycoside antibiotic with QZN 34 eradicated the mixed-species biofilm. The mechanism of action of QZN 34 toward Gram-positive bacteria is shown to involve membrane perturbation and dissipation of transmembrane potential. Graphical abstract: Highlights: QZNs inhibit PQS-dependent quorum sensing and reduce biofilm formation in Pseudomonas aeruginosa A subset of QZNs is bactericidal for planktonic Staphylococcus aureus and severely damages biofilms In mixed species biofilms, P. aeruginosa protects S. aureus from tobramycin Tobramycin plus QZN eradicates mixed P. aeruginosa and S. aureus biofilms Abstract : P. aeruginosa and S. aureus cause biofilm-associated infections. Murray et al. demonstrate that quinazolinone inhibitors of P. aeruginosa quorum-sensing can be chemically modified to kill S. aureus biofilms and prevent P. aeruginosa -mediated protection of S. aureus against tobramycin. Tobramycin plus quinazolinone eradicates mixed P. aeruginosa and S. aureus biofilms.